A pipeline for the QR update in digital signal processing. Issue 1 (24th April 2019) - Dolz, Manuel F.; Alventosa, Fran J.; Alonso-Jordá, Pedro; Vidal, Antonio M.
Abstract : The input and output signals of a digital signal processing system can often be represented by a rectangular matrix as it is the case of the beamformer algorithm, a very useful particular algorithm that allows extraction of the original input signal once it is cleaned from noise and room reverberation. We use a version of this algorithm in which the system matrix must be factorized to solve a least squares problem. The matrix changes periodically according to the input signal sampled; therefore, the factorization needs to be recalculated as fast as possible. In this paper, we propose to use parallelism through a pipeline pattern. With our pipeline, some partial computations are advanced so that the final time required to update the factorization is highly reduced.